Use of learning resources on the World Wide Web (WWW) among UTM Students In Project Based Learning for English Academic Purpose - Jaafar, Haliza; Zainal Abidin, Hafilah; Azahar, Zairus Norsiah; Hashim, Affendi (Faculty of Management and Human Resource Development, 2004)
This research is a survey on the use of learning resources on the World Wide Web (WWW) for project based learning for the subject English for Academic Communication among UTM students in Skudai, Johor Bahru. 218 UTM students from various faculties were involved in this research. Data were collected using questionnaire and analyzed using descriptive statistics. The findings indicated that in general UTM students used the learning resources on the WWW moderately for their project based learning especially for those students who are currently taking English subject UHB 1322.